(untitled) (International Journal of Scientific Research in Science and Technology, 2025)
Amid mounting efforts toward increased sustainability globally, green finance has been increasingly receiving attention because of the role the financial systems play in them. The advent of FinTech — an integration of finance with technology — has emerged as a game changer in advancing the financial literacy and adoption of financially responsible and green financial practices. This study seeks to understand the ways in which FinTech fosters green finance through greater financial access, transparency, participation, and engagement, especially in neglected demographic groups. It employs a mixed-methods approach comprised of quantitative surveys and qualitative interviews with diverse participants from different strata in India. The study found that there is a strong positive correlation between sustainable investment and financial literacy among users of FinTech platforms. This has policy implications, as well as those for financial and technology institutions, on how to use FinTech to support financial inclusion and deepen environmental responsibility.